Promoting Social and Economic Justice Through Interdisciplinary Work in Transactional Law - Susan R. Jones (Washington University Journal of Law & Policy, 2004)
This Essay explores the importance of interdisciplinary collaboration in small business within the context of community economic development (CED). Through the experience of the George Washington University Small Business Clinic (GWUSBC), one of the oldest in the United States, I hope to shed some light on the opportunities and challenges associated with cross-disciplinary work. Part I of this Essay surveys microenterprise and small business development with emphasis on minority and women entrepreneurs. Part II examines the need for legal assistance to micro-entrepreneurs and other small businesses. Part III describes the rise of small business clinical programs and discusses GWUSBC as a model. Part IV discusses George Washington University’s (GW’s) experience in interdisciplinary transactional practice and the pedagogical value of working with professionals in other disciplines. Part V explains recent developments in business law pro bono. Part VI discusses new initiatives in community development. Part VII examines transactional interdisciplinary practice within the context of the market driven ethical discussion of multidisciplinary and multijurisdictional practice. Part VIII discusses incentives and impediments to transactional interdisciplinary collaboration. Part IX presents the conclusion.
Keywords: Multidisciplinary practices; Clinical legal education; Social justice; Interdisciplinary approach in education; Minority business enterprises; Legal ethics